To-Morrow : a Peaceful Path to Real Reform. - Hall, Sir Peter (Routledge, 2003)
Ebenezer Howard's Tomorrow: A Peaceful Path to Real Reform was first published in 1898. This new facsimilie edition of the original publication has updated authoritative commentary.